Edukasi dan Sosialisasi Anti-Bullying dalam Pencegahan Kekerasan di Lingkungan Pendidikan Bangkalan - Luluk Hanifah; Dira Aadelia Oktaviana Putri; Awalinda Nur Fittyadini Arofatin; Saniyah Labibah; Maulidatus Tsaniyah; Anik Sunariyah; Siti Mutiatun (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Bullying is a serious issue that frequently occurs in school environments, negatively affecting the physical and mental well-being of victims. Adolescence, as a phase of identity formation, makes students vulnerable to involvement both as perpetrators and as victims. This article aims to provide a comprehensive description of the bullying phenomenon by discussing definitions, types, causes, impacts, and prevention strategies through education and socialization. Anti-bullying socialization activities were carried out as an effort to create a safe and supportive school environment. The implementation method included a preparation stage, material presentation by expert speakers, interactive discussion and Q&A sessions, an anti-bullying campaign, and the formation of an Anti-Bullying Task Force as a means of program sustainability. The results showed high enthusiasm and improved student understanding of the dangers of bullying, reflected in the active participation of attendees in Q&A activities and changes in attitudes toward mutual respect and non-violence. These findings indicate that education and socialization collaboratively designed by educators, parents, and communities can be an effective strategy for preventing bullying. With sustained efforts, schools can become safer, more comfortable environments that support the emotional well-being of all students.